Perspectivas da casa do amanhã o impacto das tecnologias da inteligência na máquina de morar - Alvares, Luiz Felipe Napole de Haro (2020)
The present master's degree deals with the emergent spaces of domestic permanence, an evolutionary form of refuge, that accompany the ruptures of the world in the face of a society where technological improvement is incessant, insofar as it goes beyond the limit of the body, in all senses, and the connects to the smooth world, immunologically organized by screens. We look at a modern thinking of architecture, which received the screen for the first time, and the relationship that would have with contemporary inhabit, centered on the small housing units that we see emerge throughout the city today. The methodological proposal of the present study is a qualitative analysis of urban life forms presented by media, between the screens, such as videos deposited on the YouTube platform that deal with living in miniature spaces. We tried to identify in these spaces, new modes of use and coexistence, where relationships are replaced by connections. The houses that inhabit the flow are devoid of measure